P434 Upadacitinib improved fatigue and health-related quality of life in patients with moderately to severely active Crohn's disease: Results from induction and maintenance phase 3 trials. (30th January 2023) - Ghosh, S; Feagan, B; Parra, R S; Lopes, S; Steinlauf, A; Kakuta, Y; Joshi, N; Lee, W J; Remple, V; Lacerda, A P; Zhou, Q; Xuan, S; et al.
Abstract: Background: Upadacitinib (UPA) demonstrated efficacy and safety in the phase 3 U-EXCEED (NCT03345836) and U-EXCEL (NCT03345849) induction, and U-ENDURE (NCT03345823) maintenance trials in patients (pts) with moderately to severely active Crohn's disease (CD). We evaluated the impact of UPA on health-related quality of life (QoL) in pts with CD. Methods: Clinical responders to UPA 45 mg (UPA45) in U-EXCEED and U-EXCEL induction trials were re-randomised at Week 12 (1:1:1) to UPA 15 mg (UPA15), UPA 30 mg (UPA30), or placebo (PBO) for 52 weeks of maintenance treatment in U-ENDURE; data from these induction and maintenance trials were included in this analysis. Endpoints included the percentage of pts who achieved an Inflammatory Bowel Disease Questionnaire (IBDQ) response (≥16 points), IBDQ remission (≥170 points), a meaningful within-person change (MWPC) from baseline of ≥9 points on the Functional Assessment of Chronic Illness Therapy – Fatigue (FACIT-F), and of ≥4.1 and ≥3.9 points on the 36-item Short-Form Health Survey (SF-36) physical (PCS) and mental (MCS) component summary scores, respectively, at Weeks 4/12 of induction and Week 52 of maintenance. Adjusted risk differences compared to PBO, 95% confidence intervals, and p-values were calculated based on the Cochran-Mantel-Haenszel test. Results: In U-EXCEED (n=324 UPA; 171 PBO) and U-EXCEL (n=350 UPA; 176 PBO), a greater proportion of UPA45- vs PBO-treated pts had an IBDQ response at Weeks 4 (U-EXCEED: 71.6% vs 47.6%; U-EXCEL: 71.0% vs 50.2%; p≤0.001) and 12 (U-EXCEED: 63.9% vs 44.4%; U-EXCEL: 68.4% vs 46.5%; p≤0.001; Figure 1). In UPA- vs PBO-treated pts, a greater proportion achieved IBDQ remission at Weeks 4 (U-EXCEED: 41.4% vs 22.4%; U-EXCEL: 44.2% vs 23.7%; p≤0.001) and 12 (all p≤0.001; Figure 1). At Week 12, a significantly greater proportion of UPA-treated pts vs PBO demonstrated a MWPC in FACIT-F, and SF-36 PCS and MCS from baseline (p≤0.001; Figure 1). Similar results for UPA45 vs PBO were achieved as early as Week 4 in FACIT-F (U-EXCEED: 42.3% vs 20.0%; U-EXCEL: 42.0% vs 27.0%), SF-36 PCS (U-EXCEED: 56.6% vs 37.2%; U-EXCEL: 53.0% vs 37.5%; p≤0.001) and MCS (p≤0.05). In the maintenance study U-ENDURE (n=168 UPA30; 169 UPA15; 165 PBO), a greater proportion of pts receiving UPA15 and UPA30 vs PBO achieved an IBDQ response (39.1%, 53.5% vs 20.4%), IBDQ remission (36.1%, 45.2% vs 13.5%), and a meaningful improvement from baseline in FACIT-F, SF-36 PCS and MCS through 52 weeks (p≤0.01; Figure 2). Conclusion: In pts with moderately to severely active CD, UPA treatment significantly improved fatigue, disease-specific and generic QoL, compared with PBO, as early as Week 4 of induction. The effects were sustained through 52 weeks of maintenance treatment.